2020
DOI: 10.1155/2020/8851525
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Stria Vascularis Damage Is Associated with Inflammation and Fibrosis

Abstract: The stria vascularis (SV) generates the endocochlear potential (EP) in the inner ear and is necessary for proper hair cell (HC) mechanotransduction and hearing. Cell junctions are indispensable for the establishment of compositionally distinct fluid compartments in the inner ear. Ototoxic drug cisplatin can damage SV and cause sensorineural hearing loss; however, the underlying mechanisms behind such injury are unclear. In this study, after the intraperitoneal injection of cisplatin (3 mg/kg/day for 7 days) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 56 publications
2
29
1
Order By: Relevance
“…Extraction of mRNA and quantitative real-time PCR Total RNA was extracted using an RNA extraction kit (RNeasy Mini QIAcube kit, QIAGEN, Hilden, Germany) from PBMCs, HEI-OC1 cells, and tissues samples. Relative expression of target genes was measured by quantitative real-time PCR (qRT-PCR) that was performed using an Eppendorf AG 22331 PCR machine (Eppendorf, Hamburg, Germany), as reported earlier (26). Briefly, qRT-PCR was performed using SYBR Green Premix Ex Taq (RR42LR, Takara Biotechnology, Shiga, Japan), and GAPDH was used as the housekeeping gene.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of mRNA and quantitative real-time PCR Total RNA was extracted using an RNA extraction kit (RNeasy Mini QIAcube kit, QIAGEN, Hilden, Germany) from PBMCs, HEI-OC1 cells, and tissues samples. Relative expression of target genes was measured by quantitative real-time PCR (qRT-PCR) that was performed using an Eppendorf AG 22331 PCR machine (Eppendorf, Hamburg, Germany), as reported earlier (26). Briefly, qRT-PCR was performed using SYBR Green Premix Ex Taq (RR42LR, Takara Biotechnology, Shiga, Japan), and GAPDH was used as the housekeeping gene.…”
Section: Micementioning
confidence: 99%
“…Briefly, qRT-PCR was performed using SYBR Green Premix Ex Taq (RR42LR, Takara Biotechnology, Shiga, Japan), and GAPDH was used as the housekeeping gene. Fold-change differences in mRNA expression were determined using the comparative cycle threshold method (26). The primers for house mice and humans used in this experiment are listed in Table I.…”
Section: Micementioning
confidence: 99%
“…Recently, the role of inflammation in drug-induced hearing loss has also gained attention. Zhang et al (2020) found that cisplatin induced the secretion of IL-1 β in SV, suggesting that inflammation is involved in the process of cisplatin-induced SV damage.…”
Section: Drug-induced Hearing Lossmentioning
confidence: 97%
“…Thus, the potential disease modeling applications are limited. For instance, there are cochlear and vestibular diseases, as well as certain ototoxic agents, that have their pathological impact—either directly or indirectly—on non-sensory cells of the inner ear [ 4 , 75 , 82 85 ]. Therefore, it will be essential to generate inner ear models that contain a diverse functional unit of inner ear cell types to capture complex genetic or drug-related mechanisms.…”
Section: Constructing Inner Ear Organoids: What Cells Are Missing?mentioning
confidence: 99%